Ergonomics of the workplace of the prevention principle of law no. 29783 and the job satisfaction of the administrative personnel of the headquarters of the University Private of Tacna, 2018 - Cabrera Ucharico, Elvira Ruth (2020)
The present study investigated the relationship between the ergonomics of the workplace of the Prevention Principle of Law No. 29783 and its relationship with the job satisfaction of the administrative staff of the Private University of Tacna in 2018. The research had a quantitative perspective, analytical and prospective. The design was non-experimental, of a transectional, correlational type. Sample of 61 administrative staff. The INSHT ergonomic characteristics self-perception questionnaire and the General Job Satisfaction Scale were used. Results: 3 of the ergonomic characteristics of the workplace such as adjustable seat plate height from 42 to 51 cm (p 0.040), upper edge of the backrest to the seat adjustable between 45 to 55 cm above the seat (p 0.04) and recommendations and enjoy frequent breaks of minutes every hour or every two hours for workers who perform repetitive tasks for several hours (p 0.001), which within the Prevention Principle of Law No. 29783 in certain cases requires correction, to In order to guarantee the means and conditions to protect the health and well-being of workers, the same ones that were statistically associated with the job satisfaction presented by the administrative staff of the rector's headquarters of the Private University in Tacna in 2018